Heat Transfer Studies in Tube Banks with Integral Wake Splitters - Md Seri, Suzairin; Mohideen Batcha, Mohd Faizal; Raghavan, Vijay R. (International Journal of Integrated Engineering, 2009)
This paper reports the findings from heat transfer studies with the presence of extended surfaces from tube banks which are termed as integral wake splitter plates. Employing this type of fins, investigations on heat transfer characteristics on a single circular tube as well as tube banks were carried out in cross flow of air in a rectangular duct. Experiments were carried out in the Reynolds number range 5 x 103 to 105 on a single cylinder of various splitter length-to-tube diameter ratios, L/D = 0.5, 1.0, 1.5 and 2.0. Further, tube banks consisting of 12 rows and 3 tubes per row in equilateral triangle arrangements with transverse pitch to diameter ratio, a = 2, were also investigated, the banks being made up of plain tubes or tubes with splitters. Heat transfer characteristics were studied for tubes with L/D = 0, 0.5 and 1.0 under constant heat flux conditions. Tube banks with L/D = 1.0 yielded the highest heat transfer rates. Findings from this work may be adopted to be utilized in various industrial applications such as economizer of a steam boiler, air-conditioning coils or waste heat recovery systems.